Novelties in Pitcairnia (Bromeliaceae; Pitcairnioideae): three new species from Mexico - González-Rocha, Edith; López-Ferrari, Ana Rosa; Espejo-Serna, Adolfo; Carrillo-Reyes, Pablo (Phytotaxa, 2024)
Three new species of Pitcairnia from Mexico are proposed: P. aleserratoae was found in Guerrero, Morelos, and Puebla; P. gracielae known from the Estado de Mexico and Morelos while P. pugana has been collected in Jalisco. Information on distribution, habitat and phenology is provided for each species. The new taxa are compared with P. jaliscana, P. karwinskyana, P. micheliana, P. palmeri, and P. pteropoda, species morphologically similar.